Functionalized Contorted Polycyclic Aromatic Hydrocarbons by a One‐Step Cyclopentannulation and Regioselective Triflyloxylation. (1st July 2019) - Yang, Xuan; Hoffmann, Marvin; Rominger, Frank; Kirschbaum, Tobias; Dreuw, Andreas; Mastalerz, Michael
Abstract: The oxidative cyclodehydrogenation (often named the Scholl reaction) is still a powerful synthetic tool to construct even larger polycyclic aromatic hydrocarbons (PAHs) by multiple biaryl bond formations without the necessity of prior installation of reacting functional groups. Scholl‐type reactions are usually very selective although the resulting products bear sometimes some surprises, such as the formation of five‐membered instead of six‐membered rings or the unexpected migration of aryl moieties. There are a few examples, where chlorinated byproducts were found when FeCl3 was used as reagent. To our knowledge, the direct functionalization of PAHs during Scholl‐type cyclization by triflyloxylation has not been observed. Herein we describe the synthesis of functionalized PAHs by the formation of five‐membered rings and a regioselective triflyloxylation in one step. The triflyloxylated PAHs can be used as reactants for further transformation to even larger contorted PAHs. Abstract : Eine regioselektive Bistriflyloxylierung eines polycyclischen aromatischen Kohlenwasserstoffs (PAK) erfolgt während der Cyclopentanellierung unter Scholl‐Bedingungen. OTf‐Einheiten durchlaufen palladiumkatalysierte Kreuzkupplungsreaktionen, die einen einfachen Zugang zu größeren und komplexeren PAKs ermöglichen.